2014
DOI: 10.1364/josab.31.000691
|View full text |Cite
|
Sign up to set email alerts
|

Single and double changes of entanglement

Abstract: Entanglement behavior for different classes of two qubit systems passing through a generalized amplitude damping channel is discussed. The phenomena of sudden single, double changes and the sudden death of entanglement are reported for correlated and non-correlated noise. It is shown that, for less entangled states, these phenomena appear for small values of channel strength. The effect of the channel can be frozen for these classes as one increases the channel strength. Maximum entangled states are more fragi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…(3a), where only the qubit is driven by the CERF. It is clear that, the entanglement decays slowly and the phenomena of the sudden changes of entanglement appear clearly [29]. The decay time is much larger than that depicted in Fig.…”
Section: Fig(3b)mentioning
confidence: 77%
“…(3a), where only the qubit is driven by the CERF. It is clear that, the entanglement decays slowly and the phenomena of the sudden changes of entanglement appear clearly [29]. The decay time is much larger than that depicted in Fig.…”
Section: Fig(3b)mentioning
confidence: 77%
“…In this work, we investigate the effect of the generalized amplitude damping channel on two classes of tripartite entangled states: GHZ and GHZ-like states. In this study, we try to answer the following questions: (i) Is the effect of the generalized amplitude damping channel on a tripartite states similar to that predicted for two qubit systems as shown in [4,5]?. In other words, can one freeze the effect of the generalized amplitude damping channel when tripartite state passes through it.…”
Section: Introductionmentioning
confidence: 97%
“…Practically, it is often required to send some parts of the generated entangled states from the source to remote users [1]. Each transmitted subsystem interacts with its environment locally and consequently leads to lose some of entangled properties of the multipartite system [2,3,4,5]. Consequently, the efficiency of using these decohered entangled states as quantum channels to perform quantum teleportation decreases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7], have investigated the effect of different types of noise channels on the one-norm geometric discord and showed that the effect of the noise channel can be frozen. Metwally showed that the phenomena of sudden single and double changes and the sudden death of entanglement are reported for identical and non-identical noise [8]. Also, the behavior of a multi-qubit system in the presence of the amplitude damping channel is investigated in [9], where the possibility of performing quantum teleportation with decohered states was discussed.…”
Section: Introductionmentioning
confidence: 99%